KARAKTERISTIK WIRAUSAHA DAN LINGKUNGAN EKSTERNAL TERHADAP KEBERHASILAN USAHA PADA MASA PANDEMI COVID-19 - Ninang Enti; Selmi Dedi; Dirarini Sudarwadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
This study aims to determine the effect of entrepreneurial characteristics and external environment variables on the success of restaurant culinary businesses during the COVID-19 pandemic in Manokwari Regency, either partially or simultaneously. This type of research used is a quantitative approach with associative problems. The sample in this study was 80 restaurant business actors in Manokwari Regency with a total of 408 restaurants. The method used in determining the sample is using the accidental sampling method. The data analysis technique used is multiple linear regression analysis. The results showed that the entrepreneurial characteristics variable partially had a significant effect on business success, and the results of the external environment variables partially had a significant effect on business success. The results of the simultaneous test of entrepreneurial characteristics variables and the external environment simultaneously affect business success. The conclusion of this research is that business actors can achieve business success if they are supported by strong entrepreneurial characteristics and overcome external environmental obstacles.